Determination of Flow Patterns in Vertical Upward Two-Phase Flow Channel via Void Fraction Profile - Zubir, M. A.; Ramli, Rahizar; Zainon, Mohd Zamri (Isfahan University of Technology, 2019)
Two-phase flow happens widely in the industrial plants and certain equipment. This paper attempts to study the characteristics of two-phase flow in a vertical piping system. This was achieved by comparing the void fraction, in the working fluid, by employing Constant Electric Current Method (CECM) with the actual observation using high-speed camera. The experiment requires a complete set of two-phase flow system information and was conducted based on various flow conditions. In order to carry out this experiment, the two-phase flow loop was constructed using a specific experimental apparatus and components. The flow channels were constructed using three pipes with three different inner diameters of 21.0 mm, 47.0 mm and 95.0 mm. The flow direction was vertical upward co-current flow with liquid superficial velocity range of 0.025 m/s to 3.0 m/s and gas superficial velocity range of 0.025 m/s to 3.0 m/s, depending on the size of the pipe. The flow pattern investigation focuses on experimental work, which was based on systematic observation and measurements using a high-speed camera and some measuring apparatus. The void fraction measurement using the CECM sensor was integrated into two-phase flow system with constant electric current running in the pipe and data acquisition system controlled virtually via LabVIEW software. Both result of the flow pattern and void fraction graph were then compared to determine the type of flow pattern from the void fraction graph. Information from the previous studies and experiments were collected and the assumption of any theoretical simplifications were used as a reference. According to the result, the flow pattern in pipe can be easily determined using CECM.